A cross-sectional assessment of depression, anxiety, and cognition in perimenopausal and menopausal women - Anjalee L Nagda; Manjiri Chaitanya Datar; Nilesh Mahadeo Naphade; Jyoti V Shetty (Wolters Kluwer Medknow Publications, 2023)
Introduction: Menopausal transition involves failure of ovarian function followed by cessation of menstruation. This has been said to lead to psychiatric comorbidities such as depression and anxiety. Estrogen also has beneficial effects on cognition and thus fluctuation in the same can lead to cognitive decline. Given the number of women undergoing menopause, timely screening of the comorbidities is of importance. Aims and Objectives: Our study aimed at assessment of anxiety, depression, and cognitive impairment in perimenopausal and postmenopausal women presenting in the medicine and gynecology units of a tertiary care hospital. The objectives were to screen the peri- and postmenopausal women presenting with medical and gynecological complaints for the presence of depression and anxiety and assess their cognitive function. To find association of their symptoms with psychosocial and menopausal factors with the psychiatric parameters. Settings and Design: Our study was conducted among the perimenopausal and postmenopausal women visiting gynecology and medicine units in a tertiary care hospital. One hundred and five women in the age group of 45-55 were assessed using a specialized pro forma, Beck's Anxiety Inventory, Beck's Depression Inventory, and Addenbrooke's Cognitive Examination III. Statistical Analysis Used: The results were analyzed using SPSS software (version 20.0). Results: 21.9% of females had moderate levels of anxiety, 24.76% had clinical depression, and 13.33% had mild cognitive impairment. The presence of psychosocial stressors had a significant impact on the anxiety, depression, and cognitive impairment. There was no significant association found between psychiatric parameters and peri- and postmenopausal stage as well between natural or surgical menopause.